2016
DOI: 10.1002/aenm.201600862
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Na–CuCl2 Rechargeable Battery toward Room Temperature ZEBRA‐Type Battery

Abstract: Despite a recent increase in the attention given to sodium rechargeable battery systems, they should be further advanced in terms of their energy density and reliability to successfully penetrate the rechargeable battery market. Here, a new room temperature ZEBRA-type Na-CuCl 2 rechargeable battery is demonstrated that employs CuCl 2 cathode material and nonfl ammable inorganic liquid electrolyte. The cathode delivers a high energy density of ≈580 Wh kg −1 with superior capacity retention over 1000 cycles as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…New types of rechargeable Na‐metal‐based batteries, such as RT sodium‐sulfur (Na‐S) batteries, RT sodium‐oxygen (Na‐O 2 ) batteries, and RT ZEBRA‐type sodium‐metal halide batteries, also exhibit potentials to develop high‐energy and low‐cost energy storage systems. However, there are still some key issues to be solved …”
Section: Introductionmentioning
confidence: 99%
“…New types of rechargeable Na‐metal‐based batteries, such as RT sodium‐sulfur (Na‐S) batteries, RT sodium‐oxygen (Na‐O 2 ) batteries, and RT ZEBRA‐type sodium‐metal halide batteries, also exhibit potentials to develop high‐energy and low‐cost energy storage systems. However, there are still some key issues to be solved …”
Section: Introductionmentioning
confidence: 99%
“…Recently, we demonstrated that a room‐temperature Na‐CuCl 2 battery employing nonflammable and highly conductive SO 2 ‐based inorganic liquid electrolyte showed a high energy density of ≈580 Wh kg −1 with excellent capacity retention over 1000 cycles. [ 6 ] Apart from outstanding battery performance, the Na‐CuCl 2 battery can guarantee safe operation owing to the intrinsic properties of the SO 2 ‐based inorganic liquid electrolyte such as nonflammability, five times higher Na ionic conductivity than that of organic electrolyte, and a wide operation temperature range from −40 to 60 °C. [ 7 ] However, the Na‐CuCl 2 battery has two major problems to overcome for its commercialization.…”
Section: Figurementioning
confidence: 99%
“…The Cu electrode soaked in the NaAlCl 4 ·2SO 2 electrolyte shows well‐resolved peaks between 8980 and 9000 eV, indicating the presence of Cu 2+ as well as Cu + states. [ 6,14 ] Figure 2c shows the ex situ XRD patterns of cycled electrodes with respect to the degree of reaction for the first cycle. As anticipated, the converted Cu electrode composed of CuCl and NaCl was electrochemically oxidized into CuCl 2 after charging.…”
Section: Figurementioning
confidence: 99%
“…This battery's cathode has the potential to deliver a high energy of about 580 Wh/kg with a cycling capability of >1000 and relatively high round-trip efficiency of about 97% [100]. Kim et al also maintained that this battery chemistry can be extended to copper halide materials such as CuBr 2 and CuF 2 that show exciting performances when used as cathode materials for the Na-Cu halide technology.…”
Section: High Performance Sodium Copper Chloridementioning
confidence: 99%